Perception of Farmers towards Custom Hiring Service Centres in Tumakuru District of Karnataka - Kadaraiah, Anil; Jirli, Basavaprabhu; Yarazari, Shivananda P.; Nandini, H. M.; Chaubey, P. N. (Indian Journal of Extension Education, 2022)
The study was carried out in Tumakuru district of Karnataka state during the year 2019- 20. Eight taluks and 130 farmers were selected where the Custom Hiring Service Centres were working effectively. The majority of the farmers strongly agreed with helps in overcoming the problem of labour through custom hiring service centre, for visiting farmers field after completion of the work, farmers pays only for the number of acres or number of hours used. The overall perception of farmers indicated that 43.8 % were categorized under favourable level of perception towards CHSC. The small and medium-sized farmers could not possess the modern machinery, due to high hiring charges with private vendors they were unable to take the farm machinery for the rent and some of the large farmers also were in great need of the modern machinery thus they require modern machinery through custom hiring. Hence, extension efforts need to be more strengthened to create awareness among the farming community about the services available in CHSCs.
Keywords: Custom hiring service centre; Farm machinery; Perception; Private vendors; Quality service; Small and marginal farmer